Agents and data mining interaction : 7th international workshop on agents and data mining interation, ADMI 2011, Taipei, Taiwan, May 2-6, 2011, revised selected papers - Cao, Longbing (Lecture Notes in Computer Science, 2012)
This book constitutes the thoroughly refereed post-workshop proceedings of the 7th International Workshop on Agents and Data Mining Interaction, ADMI 2011, held in Taipei, Taiwan, in May 2011 in conjunction with AAMAS 2011, the 10th International Joint Conference on Autonomous Agents and Multiagent Systems. The 11 revised full papers presented were carefully reviewed and selected from 24 submissions. The papers are organized in topical sections on agents for data mining; data mining for agents; and agent mining applications.